Pengaruh Komitmen Birokrasi dan Total Quality Management Terhadap Kualitas Pelayanan Ijin Usaha Industri (Suatu Usaha Meningkatkan Investor di Medan Sumatra Utara) - Erika Revida (KINERJA, 2009)
The fundamental problems in this research were the less of quality of industrial permit services: inefficient, ineffective, irresponsive, and unfair. The cost of services were expensive, inappropriate with standard and also length bureaucracy enchain which must pass by, so that require bureaucracy commitment and Total Quality Management. The purposes of this research were to study and analyse the influence of Bureaucracy Commitment Towards Total Quality Management, Bureaucracy Commitment Towards Quality of Industrial Permit  Service,  Total  Quality  Management  Towards  Quality  of Industrial  Permit  Service,  Bureaucracy Commitment and Total Quality Management jointly Towards Towards quality of Industrial Permit Service in Medan North Sumatera. Research method which is used in this research is survey. Sampling technique is proportional random sampling. Technique of data analyse used is path analysis. Before using path analysis, data must be change into interval scale by Method of successive interval. Test of validity instrument used by  correlation  of  Pearson  and  test  of  reliability  used  by Coefficient  of  Cronbach.  Data  are  used  in  this research are quantitative and qualitative. The Results of this research show that Bureaucracy Commitment has positive influence on Total Quality Management, Bureaucracy Commitment has positive influence on Quality of Industrial Permit Service, Total Quality Management has positive influence on Quality of Industrial Permit Service, Bureaucracy Commitment and Total Quality Management jointly have positive influence on Quality of Industrial Permit Service in Medan North Sumatera.